Risk Management Application Based on ISO 31000:2018 - A Case Study of Hypoallergenic Laundry Laboratory (LALABO) - Annisa Inas Ariyanti; Rhian Indradewa; Ferryal Abadi; Yanuar Ramadhan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
LALABO (Laundry Laboratory) is a laundry business model in Jakarta, characterized by its hypoallergenic and eco-friendly services, utilizing smart locker technology for drop points, mobile application, and personalized fragrance options. This study responds to the growing demand for skin-safe laundry services, driven by limited providers and increasing public awareness of skin health in Jakarta and other major Indonesian cities. Using a descriptive case study approach, data were collected through document analysis, observation, and organizational review. The analysis focused on designing a risk management model based on the ISO 31000:2018 framework. The findings indicate that structured risk identification, assessment, and treatment are essential for managing uncertainties in marketing, operations, human resources, and finance. LALABO can minimize potential risks and achieve operational excellence. Academically, this study expands the limited literature on ISO 31000 implementation in micro and small service enterprises, while practically it provides insights for entrepreneurs developing innovation-driven businesses.